Hope and its Relationship to Perceived Stress Among Primary Caregivers for Individuals with Hearing Disabilities (Journal Of Educational and Psychological Researches, 2025)
The research aims to explore the levels of hope and perceived stress among (n = 60) primary caregivers of children with hearing disabilities and to examine the relationship between them. Additionally, it aims to identify differences in the average scores of hope and perceived stress according to a set of demographic variables (educational level and degree of the child's hearing impairment). The adult hope scale and the perceived stress scale were applied. The descriptive correlational method was used. The research results revealed a high level of hope and a moderate level of perceived stress among the sample. Furthermore, a moderate negative relationship between hope and perceived stress was found; this was achieved by calculating the correlation coefficient between hope and perceived stress, which resulted in -0.433. The results also indicated there are no statistically significant differences in the average scores of hope and perceived stress attributed to educational level or the severity of the child's hearing impairment. Finally, the results showed that hope predicts perceived stress, explaining 17.4% of the variance in perceived stress.